Investigation into the impact of chloride ion uptake inhibitors on tobacco plants - Ding, Hai; Wang, Shengli; Zhang, Yan; Dong, Jianfei; Zhang, Ruonan; Zhang, Bao; Ma, Shangyi; Liu, Dong; Cui, Ruibin; Chen, Bin; Wang, Qun; Sun, Jian; et al. (Frontiers in Soil Science, 2025)
IntroductionExcessive chloride ion content in tobacco leaves adversely affects the flammability of flue-cured tobacco, particularly in tobacco-growing regions of northern China, where this issue is more pronounced. Consequently, this poses a challenge for finding economically and environmentally friendly control methods. Vibrio natriegens, as a non-pathogenic, moderately halophilic bacterium, can reduce chloride ion content in soil. Zn²+, as a chloride ion channel inhibitor, can effectively reduce the accumulation of chloride ions in plants.MethodsIn this study, we established two experimental groups, T1 and T2, where T1 contained V. natriegens as a chloride ion inhibitor and T2 contained Zn²+ as a chloride ion inhibitor. We investigated the effects of T1 and T2 on chloride ion content in tobacco, soil environmental factors, and microbial community structure. Various methods were employed to measure soil physicochemical properties, and the impact of different treatments on microbial community structure was elucidated through soil microbial DNA extraction, PCR amplification, PE library construction, Illumina sequencing, and subsequent bioinformatics analysis.Results and discussionThe results indicate that both inhibitors significantly reduced chloride ion levels in tobacco (p < 0.05) and altered the abundance of certain soil microorganisms. Specifically, the chloride ion content in upper leaves decreased from 1.33% to 0.83% under T1 treatment, while the T2 experimental group showed a reduction to 0.99%. Additionally, we evaluated the agronomic traits of tobacco plants and found that the application of chloride ion inhibitors promoted plant growth. Field trials further validated the efficacy of these inhibitors, with treated tobacco leaves exhibiting significantly lower chloride ion content compared to the control group. This study, based on the source of chloride ion uptake by tobacco plants from soil, employed strategies to control soil chloride ion content or reduce plant uptake, thereby effectively managing chloride ion levels in tobacco leaves. This provides an effective strategy for controlling chloride ion content in tobacco leaves, contributing to the high-quality development of tobacco production.